2016
DOI: 10.1007/s00209-016-1749-z
|View full text |Cite
|
Sign up to set email alerts
|

Local average in hyperbolic lattice point counting, with an Appendix by Niko Laaksonen

Abstract: The hyperbolic lattice point problem asks to estimate the size of the orbit Γz inside a hyperbolic disk of radius cosh −1 (X/2) for Γ a discrete subgroup of PSL2(R). Selberg proved the estimate O(X 2/3 ) for the error term for cofinite or cocompact groups. This has not been improved for any group and any center. In this paper local averaging over the center is investigated for PSL2(Z). The result is that the error term can be improved to O(X 7/12+ε ). The proof uses surprisingly strong input e.g. results on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…In the appendix to [21] Laaksonen provides numerics that support this conjecture. In the proof of Theorem 1.4 (see Proposition 4.5) we prove that we have…”
Section: Introductionmentioning
confidence: 80%
“…In the appendix to [21] Laaksonen provides numerics that support this conjecture. In the proof of Theorem 1.4 (see Proposition 4.5) we prove that we have…”
Section: Introductionmentioning
confidence: 80%
“…Petridis and Risager [, Conjecture 2.2] conjectured square root cancellation in sum , namely Sfalse(T,Xfalse)T(TX)ε.Furthermore, they showed that estimate yields not only the best possible error term O(X1/2+ε) in the prime geodesic theorem, but also the best error term on average for the hyperbolic lattice problem. See for more details.…”
Section: Introductionmentioning
confidence: 99%
“…In [, Appendix], Laaksonen proved that the conjecture of Petridis and Risager is true for a fixed X as T. Moreover, for κfalse(Xfalse):=X1/2+X1/2,where x is the distance from x to the nearest integer, Laaksonen mentioned in [, Experimental Observation 2] that S(T,X) has a peak when κ(X)=0.…”
Section: Introductionmentioning
confidence: 99%
“…More information can be obtained for the error term when the group Γ is arithmetic. For Γ = PSL 2 (Z), Petridis and Risager recently studied the average growth of E(X; z, z) on compact subsets of the modular surface Γ\H both in the local [31] and the discrete aspect [32]. To state their discrete average result, for d < 0 a fundamental discriminant denote by Λ d the set of CM (or Heegner) points of discriminant d and by h(d) the class number h(d) = #Λ d .…”
Section: Introductionmentioning
confidence: 99%